1999
DOI: 10.1097/00005650-199903000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Ambulatory Care Groups in the Primary Care of a European National Health Care System

Abstract: Those results support the inadequacy of using the patient's age and sex alone to estimate physicians' workload in the primary health setting and the need to consider morbidity categories. The ACGs case-mix system is a useful tool for incorporating patients' morbidity in the explanation of the use of primary health care services in a European national health system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
6

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 11 publications
2
33
0
6
Order By: Relevance
“…The model identifi ed 4 ADGs that signifi cantly increased the risk of a patient being a persistently high user of primary care visits. These ADGs were chronic medical-unstable (11); see and reassure (30); psychosocial: time limited, minor (23); and signs/symptoms, minor (26). ADG 33 for pregnancy was negatively associated with the persistence of clinic visits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model identifi ed 4 ADGs that signifi cantly increased the risk of a patient being a persistently high user of primary care visits. These ADGs were chronic medical-unstable (11); see and reassure (30); psychosocial: time limited, minor (23); and signs/symptoms, minor (26). ADG 33 for pregnancy was negatively associated with the persistence of clinic visits.…”
Section: Resultsmentioning
confidence: 99%
“…22,23 For this study, we used the Johns Hopkins adjusted clinical groups (ACGs) system to categorize patients into diagnosis groups. [24][25][26] ACGs were developed by a team including medical experts in primary care to be both clinically meaningful and predictive of utilization and resource costs. ACGs are currently used by managed care plans and others for risk-adjusting fi nancial arrangements with providers and for physician profi ling.…”
Section: Clinical Risk Factorsmentioning
confidence: 99%
“…Different but complementary perspectives on the prevalent morbidity in these cases can be verified through the Aggregated Diagnosis Groups (ADGs) and Extended Diagnosis Clusters (EDCs) [31]. Other studies have shown that recognizing the complexity of cases, in terms of both outpatient [32][33][34][35] and hospital care [36][37][38], can lead to optimized and patient-oriented management strategies and solutions. In the state of São Paulo, stratification adjusted for risk factors together with underlying morbidity can help to identify improvement opportunities, policy strategies for allocation of differentiated resources, or cases where there is a need to structure more complex services so that procedures in cardiac surgeries can be done.…”
Section: Discussionmentioning
confidence: 99%
“…Both have been developed as a result of academic endeavours [19][20][21][22] and both have been subject to independent testing, including on populations outside the US. [23][24][25] Examples of categories in the systems are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%